S-Equol enhances osteoblastic bone formation and prevents bone loss through OPG/RANKL via the PI3K/Akt pathway in streptozotocin-induced diabetic rats - Xu, Zhe; Xu, Jing; Li, Shuo; Cui, Hanqiang; Zhang, Guiming; Ni, Xiangmin; Wang, Jian (Frontiers in Nutrition, 2022)
Background: This study aimed to explore whether S-Equol delays diabetes-induced osteoporosis and the molecular mechanisms underlying its therapeutic effects. Materials and methods: Thirty-five male Sprague–Dawley rats were randomized into five groups. The diabetic osteoporosis (DOP) group and three S-Equol treatment groups were intraperitoneally injected with streptozotocin (STZ) to develop a DOP model. After the 12-week intervention, bone transformation indicators were detected using an enzyme-linked immunosorbent assay kit; bone mineral density (BMD) and bone microstructure were obtained using dual-energy X-ray absorptiometry and microCT; morphological changes in the bone tissue were investigated using HE staining; and bone morphogenetic proteins were detected using immunohistochemical staining. ROS17/2.8 cells were cultured in vitro, and Cell Counting Kit-8 was used to test the protective effects of S-Equol in osteoblastic cells in a high-fat and high-glucose environment. Furthermore, the expression of osteoprotegerin (OPG), receptor activator of nuclear factor kappa-B ligand (RANKL), estrogen receptor β(Erβ), phosphorylated Akt (pAKT)/ protein kinase B (AKT), and osteocalcin (OC) in bone tissue and ROS17/2.8 cells was assessed using reverse transcription polymerase chain reaction (RT-PCR) and western blotting. To determine whether ERβ and phosphatidylinositol 3' -kinase (PI3K)/AKT signaling pathways are involved in the process, LY294002 (PI3K signaling pathway inhibitor) and small interfering RNA targeting ERβ mRNA (si-ERβ) were used to verify the function of the ERβ-mediated PI3K/AKT pathway in this process. Results: After the 12-week intervention, S-Equol enhanced BMD, improved bone microarchitecture in DOP rats (P<0.05), and improved markers of bone metabolism (P<0.05). In vitro, 10−6 mmol/L S-Equol was selected to significantly protect osteoblasts from high- and high-glucose environments (P<0.05). Gene expression of OPG, ERβ, pAKT/AKT, and OC was upregulated compared to the DOP group, and RANKL was downregulated compared to the DOP group (P<0.05) both in bone tissue and osteoblastic cells. The promotion of OPG and pAKT/AKT is mediated by LY294002 and siERβ. Conclusion:S-Equol binds to ERβ to regulate OPG/RANKL via the PI3K/AKT pathway and improve DOP. Our results demonstrate the potential role of S-Equol in the treatment of DOP by targeting ERβ. Thus, S-Equol may have the potential to be an adjuvant drug for treating DOP.